Environmental and social-economic impacts of sewage sludge treatment : - Zhang, Guofeng (Springer, 2016)
This book presents an experimental simulation of sewage treatment, which is designed to evaluate the environmental and social-economic impacts of integrated sewage treatment policies. The author puts forward a comprehensive linear optimization simulation model that takes the environmental, energy and economic systems into consideration. Beijing was selected as a typical Chinese city for the purposes of simulation, and the comprehensive model employed realistically reflects the specific and unique characteristics of Beijing's social economy and environmental status. Given the importance of sewage treatment and the accurate assessment of its impacts, the book will be of interest to researchers and scholars of environmental economics.